Phased array antenna design for 5G mobile networks - Habaebi, Mohamed Hadi; Janat, Mohanad; Islam, Md Rafiqul (Asian Research Publishing Network (ARPN), 2015)
In the next few years, the demands and challenges for the 4G (and its derivatives ie LTE-A) alternative must be addressed to meet the prime objectives of the upcoming 5G mobile networks such as increased capacity, improved data rate, low latency, and better quality of service. To achieve these objectives, drastic improvements need to be made in cellular network architecture and the antenna configuration that is used for this purpose. This paper presents the results of a detailed survey on the fifth generation (5G) cellular network architecture and some of the key emerging technologies that are helpful in improving the architecture and meeting the evasively increasing demand ofusers. In this detailed survey, the prime focus is on the 5G cellular network architecture, massive multiple input multiple output (MIMO) technology, and millimetre wave beamforming technologies. In this paper, a general probable 5G cellular network phased array antenna concept is proposed, which shows that a combination of multipleinput multiple output and the beamforming can be utilized at the same time to overcome the limitation of either systems.